Preliminary analysis of dust storm effects on microwave links measured in Khartoum - Elsheikh, Elfatih A. A.; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Ismail, Ahmad Fadzil; Chebil, Jale (IEEE, 2015)
A field study on dust storm effect on Microwave links in arid area covering a wide range of radio frequency was conducted for seven months in Khartoum, Sudan. The study involves computerized monitoring of Transmitted and Received signal levels of (TRSL) of six Microwave links operating at Ku (14GHz) and Ka (21GHz) bands as well as an automatic weather station. This paper presents a description of the experiment and reports preliminary results of measuring dust storms as they affect the radio wave propagation at Ku and Ka bands. The effect of dust storms on propagation is studied by measuring the storm parameters; visibility and induced attenuation due to these storms. The preliminary result shows that the higher frequency is more affected by dust storms than the lower. In addition, the attenuation increases with lengths of the link. Key Words-dust storm attenuation, visibility, microwave links.